What is your educational philosophy? Modern and postmodern approaches to foreign language education - Uzun, Levent (Studies in Second Language Learning and Teaching, 2012)
The present study discusses the concepts of education and training, while also highlighting the paradigm wars of the positivistic and naturalistic views, beginning with the age of ancient philosophies and continuing to the latest era of postmodernism. Additionally, language education is examined considering the linguistic and educational fundamentals which all need to be based on and combined by a philosophy. The research in foreign language (FL) education is evaluated from both the teaching and learning perspectives in order to reach conclusions concerning the current situation and the requisites of futuristic and innovative FL education. What is my educational philosophy? is proposed as a key question that not only FL teachers but also all educators should ask themselves; a question that will guide teachers throughout their entire lives and illuminate their minds throughout their teaching practice. Teacher and learner roles are discussed in order to determine whether teachers or learners should come first in the process of education. It is emphasised that the philosophical perspectives of education urgently need to be built into the minds of educators prior to asking them to convey knowledge of any kind or to apply the materials of a specific teaching method. The study concludes with the observation that there exists a serious discrepancy between the needs, preferences and interests of the learners and the views held by educational decision makers, who seem to fail to catch up with the trends in technology and globalisation.